Delivery Mode Shapes the Composition of the Lower Airways Microbiota in Newborns - Cardelli, Elisa; Calvigioni, Marco; Vecchione, Alessandra; Macera, Lisa; Mazzantini, Diletta; Celandroni, Francesco; Panattoni, Adelaide; Pistello, Mauro; Maggi, Fabrizio; Ghelardi, Emilia; Mannella, Paolo (Frontiers in Cellular and Infection Microbiology, 2021)
Radical alterations in the human microbiota composition are well-known to be associated with many pathological conditions. If these aberrations are established at the time of birth, the risk of developing correlated pathologies throughout life is significantly increased. For this reason, all newborns should begin their lives with a proper microbiota in each body district. The present study aimed at demonstrating a correlation between the mode of delivery and the development of a well-balanced microbiota in the lower airways of newborns. 44 pregnant women were enrolled in this study. Microbiological comparative analysis was carried out on tracheobronchial secretions of babies born through vaginal delivery (VD) or caesarean section (CS). All samples showed the presence of bacterial DNA, regardless of the mode of delivery. No viable cultivable bacteria were isolated from the CS samples. On the contrary, VD allowed colonization of the lower airways by alive cultivable bacteria. The identification of bacterial species revealed that Lactobacillus spp. and Bacteroides vulgatus were the most common microorganisms in the lower airways of vaginally-delivered newborns. Data obtained from quantitative PCRs showed a significantly higher total bacterial load, as well as Firmicutes and Lactobacillus spp. amount in VD samples than CS ones, while no statistically significant difference was found in Torque Teno Virus (TTV) load between samples. Taken together, our findings confirm the hypothesis that passage through the maternal vaginal canal determines more beneficial colonization of the lower airways in newborns.